Impact of climate change on regional irrigation water demand in Baojixia irrigation district of China - Wang, Xiao Jun (Springer Netherlands, 2016)
Water scarcity in China would possibly be aggravated by rapid increase in water demand for irrigation due to climate change. This paper focuses on the mechanism of climate change impact on regional irrigation water demand by considering the dynamic feedback relationships among climate change, irrigation water demand and adaptation measures. The model in implemented using system dynamics approach and employed in Baojixia irrigation district located in Shaanxi Province of China to analyses the changes in irrigation water demand under different climate change scenarios. Obtained results revealed that temperature will be the dominant factor to determine irrigation water demand in the area. An increase of temperature by 1 °C will result in net irrigation water demand to increase by about 12,050 × 104 m3 and gross water demand by about 20,080 × 104 m3 in the area. However, irrigation water demand will not increase at the same rate of temperature rise as the adaptation measures will eventually reduce the water demand increased by temperature rise. It is expected that the modeling approach presented in this study can be used in adopting policy responses to reduce climate change impacts on water resources.